Imaging Findings of Liposuction with an Emphasis on Postsurgical Complications - You, Je Sung (Korean J Radiol, 2015)
Liposuction is one of the most frequently performed cosmetic surgeries worldwide for reshaping the body contour. Although liposuction is minimally invasive and relatively safe, it is a surgical procedure, and it carries the risk of major and minor complications. These complications vary from postoperative nausea to life-threatening events. Common complications include infection, abdominal wall injury, bowel herniation, bleeding, haematoma, seroma, and lymphoedema. Life-threatening complications such as necrotizing fasciitis, deep vein thrombosis, and pulmonary embolism have also been reported. In this paper, we provide a brief introduction to liposuction with the related anatomy and present computed tomography and ultrasonography findings of a wide spectrum of postoperative complications associated with liposuction.